Experimental investigation of flush end-plate connection on cruciform column section [electronic resource] - Lim, Chia Wei, 1988-; Shek, Poi Ngian, supervisor (2012)
Project Paper (Sarjana Muda Kejuruteraan (Awam))- Universiti Teknologi Malaysia, 2012